Transient early increase in echocardiographically estimated pulmonary artery pressure after closure of a large patent ductus arteriosus in an adult: a case report - Peng Dai; Rui Xu; Yifan Yan; ZiHan Liang; Zongwei Xiao (Frontiers in Medicine, 2026)
Pulmonary artery pressure generally decreases after closure of a patent ductus arteriosus (PDA) following elimination of abnormal left-to-right shunting. However, transient increases in echocardiographically estimated pulmonary artery pressure may occasionally occur during the early postoperative period. We report a 41-year-old woman with a large tubular PDA and echocardiographic evidence of pulmonary hypertension. Preoperative computed tomography angiography demonstrated a PDA measuring approximately 13 mm in diameter and 17 mm in length. Echocardiography showed predominantly left-to-right shunting, left atrial and left ventricular enlargement, and an estimated systolic pulmonary artery pressure (SPAP) of 63 mmHg. Right heart catheterization demonstrated a pulmonary vascular resistance of 1.25 Wood units, a transpulmonary gradient of 14 mmHg, and a pulmonary artery wedge pressure of 23 mmHg, findings that argued against advanced fixed pulmonary vascular obstruction and suggested an important high-flow/post-capillary component. After surgical PDA closure, echocardiographically estimated SPAP transiently increased to 101 mmHg on postoperative day 3, accompanied by right ventricular enlargement and reduced left ventricular dimensions. Estimated SPAP subsequently decreased to 60 mmHg on postoperative day 8 and to 38 mmHg at 1 month, with normalization of right-heart dimensions and marked clinical improvement. Diuretics and macitentan were administered during the postoperative period; however, the relative contributions of medical therapy, changes in volume status, postoperative cardiovascular adaptation, and spontaneous recovery cannot be determined from this single case. Because postoperative invasive hemodynamic reassessment was unavailable, the mechanism underlying the transient increase in estimated SPAP remains uncertain. This case illustrates that a marked early rise in echocardiographically estimated SPAP after PDA closure may be transient and should be interpreted in conjunction with serial echocardiographic findings, clinical status, and available hemodynamic data.